Invent good memories if you don't have any fiction and nonfiction - Roldan, Sandra Nicole C. (2010)
This MA creative writing thesis is a collection twelve essays and seven short stories that interrogate the workings of memory and invention vis-a-vis the artful shaping of a text. The section entitled Here, Now contains more direct confrontations of memory and narrative, pieces that explore the idea of closeness-to facts and of relationships. Away brings together stories and essays that chronicle the strangeness of living in a foreign country, representing a veering away from hard facts. The narratives in Return signify a return to home, as well as a return to an earlier time-topics that the writer keeps returning to in writing. The entire collection demonstrates how the writer's notions of fact, memory, narrative, and invention have evolved. The introductory essay collects various opinions on craft and ethics, and discusses the need to write and to remember, the process of waiting for a story, how the physical tools for writing can help shape the text. There is also a brief survey of CNF published as of 2009, including the possibilities that technology, new media, and social networking sites bring into the craft of writing.
Thesis (M.A. Creative Writing)--University of the Philippines, Diliman.
Keywords: Philippine essays (English).; Short stories, Philippine (English).